(untitled) - Michael J. Singer (New Jersey, 2002)
This text provides a fresh look at soil science. The goal is to help students understand the parts that contribute to the whole soil individual and then appreciate how those parts function together. It begins by assembling the parts (solid, liquid and gas phases) of a soil, followed by explaining the interactions among the parts. Subsequently, genesis, classification, and interpretation of soil properties are explained.
Keywords: Land use,rural,Soil science,Plant; Soil relationships